(untitled) (Research, Society and Development, 2021)
There are different options for botulinum neurotoxin such as A, B, C, D, E, F and G. Types A and B are the most used in dental practice. They can have a well-known controlled effect on muscle tissue. Botulinum toxin has become a medicine used for functional purposes in dentistry and recently used for facial cosmetic purposes. Its indication stands out in patients with masseter hypertrophy, among others. This academic work aims to describe, through a literature review, the use of botulinum toxin in cases of masseter hypertrophy. For that, a qualitative research of secondary source, descriptive with deductive method was used. The use of botulinum toxin for the treatment of masseter hypertrophy has been increasingly highlighted, as its application is very safe and efficient. However, studies that prove the importance of its use are still scarce.